Analisis Total Electron Content (TEC) Menggunakan Continous Wavelet Transform Sebagai Indikator Prekursor Gempa Bumi Di Wilayah Provinsi Bengkulu - Laksamana Agung Aprillo; Hendy Santosa; Faisal Hadi (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2019)
ABSTRACT Bengkulu is one of 34 provinces in Indonesia which is a megathrust region. So Bengkulu province is often hit by many large earthquakes with shallow depth. TEC anomaly was analyzed based on three electromagnetic waves radiated by an earthquake. The total electron content (TEC) anomaly is seen through the global positioning system (GPS) dual-frequency radio signal data. The continuous wavelet transform (CWT) method is used to divide the signal analysis into several sections according to the electromagnetic wave frequency range of acoustic (2.5 mHz) -3 mHz), gravity waves (1 mHz-2.8 mHz) and rayleigh waves (5 mHz-33 mHz). GPS observation data for 9 days is calculated using the Standard deviation (2?) method to see trends in data changes. The analysis shows anomalies in the September 12 2007 earthquake (7.9 Mw), the March 5 2010 earthquake (6.3 Mw) and the August 4 2011 earthquake (6.0 Mw). Anomalies are detected 1 to 5 hours before an earthquake occurs. TEC anomalies that occur may be related to the process of preseismic before the earthquake and may be an early sign of an earthquake.Keyword: earthquake, total electron content, continous wavelet transform, standard deviation